The Critical Role of the Oncology Nurse as a Partner in the Management of Patients With Advanced Kidney Cancer: Toxicity Management, Symptom Control, and Palliative Care. Issue 5 (September 2020) - Moldawer, Nancy P.; Wood, Laura S.
Abstract : Abstract: The treatment of advanced renal cell carcinoma has changed dramatically since 2005 with the approval of 12 regimens including oral, intravenous, and combination strategies. These approvals have changed the treatment paradigm for these patients and developed new challenges and a critical role for oncology nurses to ensure that the treatment plan and adverse events are managed effectively. The majority of these regimens include an oral anticancer drug, which requires patients and their caregivers to understand the medication, the potential adverse events, the importance of medicine adherence, and the importance of early and ongoing education with the oncology team to maximize clinical outcomes. The evolution of the role of the nurse in meeting this need and its critical contribution to the comprehensive care of the kidney cancer patient will be reviewed.